Estudo do aproveitamento de resíduo de gesso como carga para compósito com matriz de resina expansiva de mamona - Oliveira Neto, Manoel Leonel de (2012)
In the execution of civil engineering works, either by wasting during the coating of wall or demolition of gypsum walls, the generation of the gypsum waste involves serious environmental concerns. These concerns are increased by the high demand of this raw material in the sector and by the difficulties of proper disposal byproduct generated. In the search for alternatives to minimize this problem, many research works are being conducted, giving emphasis in using gypsum waste as fillers in composites materials in order to improve the acoustic, thermal and mechanical performances. Through empirical testing, it was observed that the crystallization water contained in the residue (CaSO4.2H2O) could act like primary agent in the expanding of the polyurethane foam. Considering that polyurethane produced from vegetable oils are biodegradable synthetic polymers and that are admittedly to represent an alternative to petrochemical synthetic polyurethane, this research consist an analysis of the thermal behavior of a composite whose matrix obtained from a resin derived from the expansive castor oil seed, with loads of 4%, 8%, 12% and 16% of gypsum waste replacing to the polyol prepolymer blend. Contributors to this analysis: a characterization of the raw material through analysis of spectroscopy by Fourier transform infrared (FTIR), chemical analysis by X-Ray Fluorescence (XRF) and mineralogical analysis by X Ray Diffraction (XRD), complemented by thermo gravimetric analysis (TGA). In order to evaluate the thermo physical properties and thermal behavior of the composites manufactured in die closed with expansion contained, were also carried tests to determine the percentage of open pore volume using a gas pycnometer, scanning electronic microscopy (SEM), in addition to testing of flammability and the resistance to contact with hot surfaces. Through the analysis of the results, it appears that it is possible to produce a new material, which few changes in their thermo physical properties and thermal performance, promotes significant changes and attractive to the environment